An investigation on the impact of combined microfiber-microcrystalline cellulose addition on the performance of Portland cement composites - Géssica Katalyne Bilcati; Marienne do Rocio de Mello da Costa; Sarah Honorato Lopes da Silva Tamura; Henrique Ajuz Holzmann (Revista IBRACON de Estruturas e Materiais)
Abstract The study of the effects of cellulosic materials as additives in matrices based on mineral binders is essential for the development of high-performance and more durable construction materials. In this context, the present research aims to propose composite systems incorporating cellulose microparticles and microfibers into cementitious matrices. The proposed systems were developed using CP V ARI cement, with cellulose microfiber (FC) contents of 0.5%, 1%, and 1.5%, along with crystalline microcellulose (MCC) contents of 0.4%, 0.6%, and 0.8%. The impact of cellulose microfiber and crystalline microcellulose on compressive strength, flexural tensile strength, mineralogy, and microstructure of cementitious composites was evaluated. The gradual increase in the combined additions of cellulose microfiber and crystalline microcellulose led to a reduction in mechanical properties. The diffraction patterns of the FC-MCC cellulose-added composites were similar to those of Portland cement composites without additives. The combinations of FC 0.5-MCC 0.4, FC 1.0-MCC 0.4, and FC 0.5-MCC 0.6 contents promoted a higher degree of hydration, resulting in superior compressive strength performance compared to cementitious composites without these materials.